Increasing Achievement Learning of Social Science on Islamic Kingdom Materials in Indonesia Through the Team Quiz Plus Method - Endang Susilowati; Sri Setyowati; R. Mendrika Vatosoa Idealy (Universitas Negeri Surabaya, 2024)
The purpose of this study was to determine the increase in student achievement in social studies learning on the subject